1996
DOI: 10.4319/lo.1996.41.5.0985
|View full text |Cite
|
Sign up to set email alerts
|

Potential methane emission from north‐temperate lakes following ice melt

Abstract: Methane, a radiatively active "greenhouse" gas, is emitted from lakes to the atmosphere throughout the open-water season. However, annual lake CH, emissions calculated solely from open-water measurements that exclude the time of spring ice melt may substantially underestimate the lake CH, source strength. We estimated potential spring CH4 emission at the time of ice melt for 19 lakes in northern Minnesota and Wisconsin. Lakes ranged in area from 2.7 to 57,300 ha and varied in littoral zone sediment type. Regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
189
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(201 citation statements)
references
References 27 publications
8
189
4
Order By: Relevance
“…Methanotrophs consume 17 % of this dissolved CH 4 during the spring and summer periods. Michmerhuizen et al (1996) found that an insignificant portion of CH 4 dissolved in Minnesota and Wisconsin lakes is oxidized during spring ice melt. If we similarly assumed no methanotrophy during the spring ice-melt periods in the model, spring diffusion emissions would increase by a factor of 2.8 and total atmospheric emissions during the study period would increase by 4.3 %.…”
Section: A4 Methane Emissions During Spring Meltmentioning
confidence: 99%
See 2 more Smart Citations
“…Methanotrophs consume 17 % of this dissolved CH 4 during the spring and summer periods. Michmerhuizen et al (1996) found that an insignificant portion of CH 4 dissolved in Minnesota and Wisconsin lakes is oxidized during spring ice melt. If we similarly assumed no methanotrophy during the spring ice-melt periods in the model, spring diffusion emissions would increase by a factor of 2.8 and total atmospheric emissions during the study period would increase by 4.3 %.…”
Section: A4 Methane Emissions During Spring Meltmentioning
confidence: 99%
“…The CH 4 content of bubbles decreases as they are encapsulated, which suggests CH 4 dissolution into the water column (Walter et al, 2008). Dissolved CH 4 accumulates in many lakes during the ice-cover period due to the slowdown or inactivity of methanotrophs in the cold, often anoxic water column (Michmerhuizen et al, 1996;Phelps et al, 1998;Boereboom et al, 2012), so dissolved CH 4 from bubbles may not be immediately subject to oxidation. However, it can potentially be oxidized when oxygen is reintroduced during spring ice melt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurately placing freshwaters in the global CH 4 budget requires a better understanding of the controls and contributions of CH 4 from different sources [2][3][4][5] . In this regard, the surface waters of lakes and rivers are systematically supersaturated with CH 4 , and it has been traditionally assumed that this CH 4 is derived from anoxic environments, via vertical and lateral transport from profundal and littoral sediments 3,[6][7][8] . This assumption certainly holds for small, shallow ecosystems where the surface layers are in relatively close contact with sediments.…”
mentioning
confidence: 99%
“…M ethane (CH 4 ) emissions currently contribute B20% to the planet's greenhouse effect, with a large, but poorly defined, fraction derived from freshwater ecosystems [1][2][3][4] . Accurately placing freshwaters in the global CH 4 budget requires a better understanding of the controls and contributions of CH 4 from different sources [2][3][4][5] .…”
mentioning
confidence: 99%